The Antagonist Visual Framing of Soekarno in Kompas Daily‘s 1966 Photo Selection - Besman, Abie; Hidayat, Dadang Rahmat; Saputra, Sandi Jaya (Jurnal Kajian Jurnalisme, 2025)
This paper examined Kompas Daily’s editorial framing strategy in depicting President Soekarno as an antagonist during Indonesia’s 1966 political turbulence. It investigated how the newspaper used visual framing, photo selection, and headline composition to construct contrasting images of Soekarno and his successor, Soeharto. Employing a qualitative method with visual and contextual analysis, this research analyzed the symbolic representation of leadership transition in Kompas’s front-page layout published on February 23, 1967. The findings revealed that Kompas framed Soekarno as a declining and melancholic figure while Soeharto was presented as confident and resolute. These visual choices were not neutral but tendentious in shifting political power, allowing Kompas to adapt to the rise of the New Order regime. The study introduces the concept of “swinging journalism” to describe the maneuver of media institutions to survive during the changing political climates. This framing positioned Kompas as not only a chronicler of events but also an agent that legitimized the New Order through subtle visual rhetoric. The paper suggested that visual media could shape public memory and political legitimacy during transitional periods. Therefore, it contributes to the growing body of literature on media representation, newsroom dynamics, and the visual construction of political narratives in authoritarian contexts. Furthermore, this study presents a case-specific illustration of editorial decision-making and ideological positioning in Indonesia’s press history, and contributes conceptual perspectives relevant to broader media studies.